The rhetorical image in women 's speech: (As opposed to the sermons of Mrs. Fatima (on her Peace) and the speeches of Ms. Zeinab (on her Peace - Jbaar, Nsrien Staar (Al-Adab Journal, 2019)
The rhetoric is an authentic art of the Arabs and an effective means of communicating ideas, expressing visions and influencing the communicator and making him convinced. The rhetoric has been associated with the pilgrims as their essence and the khateeb have an influential role in the success of the Hajj process and laying the foundations of the artificial construction of those who are addressing them. To achieve justice and enable the arguments and the credibility of evidence and enjoy the authority to qualify him to influence the hearts of the interviewers and knowledge of their levels have been available in these qualities in the personality of Ms. Zahra peace be upon her and the identity of Ms. Zainab peace be clear and clear and her speeches on TB The graphic performance embodied in the image formation was characterized by its high ability to produce the meaning of its energy. The image in the sermons was a pilgrimage of its various levels, as it was derived from the worlds of the recipients and their cultural